Expertise and forms of knowledge in the government of families - Murphy, Elizabeth (Blackwells, 2003)
This paper examines the relationship between the state and the individual in relation to an aspect of mundane family life – the feeding of babies and young children. The nutritional status of children has long been a matter of national concern and infant feeding is an aspect of family life that has been subjected to substantial state intervention. It exemplifies the imposition upon women the ‘biologico-moral responsibility’ for the welfare of children (Foucault 1991b). The state’s attempts to influence mothers’ feeding practices operate largely through education and persuasion. Through an elaborate state-sponsored apparatus, a strongly medicalised expert discourse is disseminated to mothers. This discourse warns mothers of the risks of certain feeding practices and the benefits of others. It constrains mothers through a series of ‘quiet coercions’ (Foucault 1991c) which seek to render them self-regulating subjects. Using data from a longitudinal interview study, this paper explores how mothers who are made responsible in these medical discourses around child nutrition, engage with, resist and refuse expert advice. It examines, in particular, the rhetorical strategies which mothers use to defend themselves against the charges of maternal irresponsibility that arise when their practices do not conform to expert medical recommendations.